Design, synthesis and screening of indole acetic acid-based tri-azo moieties as antioxidants, anti-microbial and cytotoxic agents - Javaid, Maryam; Haq, Ihsan-Ul; Nadeem, Humaira; Fatima, Humaira; Khan, Arif-Ullah; Irshad, Nadeem (Frontiers in Pharmacology, 2023)
Multidrug resistance and infectious disease have enormous spread despite drug discovery and development advancements. 1, 2, 4 -triazoles have been extensively studied, playing an imperative role in many pathologic conditions. A series of Schiff base triazoles; derived from Indole -3- acetic acid with substituted Benzaldehydes (5a-5g) were designed, synthesized, and evaluated through various Spectroanalytical techniques. SwissADME was used to assess physicochemical properties and pharmacokinetic drug-likeliness behavior. (5a-5g) were evaluated for their varied biological potential through antioxidant, antimicrobial, enzyme inhibition, and cytotoxic evaluation. Schiff bases express drug-like nature as they follow Lipinski’s rule of five. 5b showed good antioxidant potential in total antioxidant capacity (TAC) and total reducing power (TRP) assays and was most active in the library in % free radical scavenging assay (%FRSA), showing 32% inhibition at 50 μg/mL concentration. Compounds showed antibacterial activity against various tested strains. 5e and 5f showed a minimum inhibitory concentration (MIC) value of 3.12 μg/mL for P.aeruginosa and K.pneumoniae, respectively. In the antifungal assay, only 5e inhibited one strain with a zone of inhibition >6 mm. These synthetic molecules possess good cytotoxic potential in the Brine Shrimp Lethality screening; 5c, 5d, and 5f exhibited LC50 =5.7 μg/mL. In the protein kinase inhibition assay, 5a, 5b, and 5g demonstrated inhibitory potential, showcasing the zone of inhibition as 7.5–10.5 mm for the bald one and 6–7.5 for the clear zone. These findings suggest that the compounds have antibacterial and cytotoxic potential, and there is a chance for further research and development in this area.